Metodologiczne podstawy współczesnej teorii politycznej (Świat Idei i Polityki, 2006)
The above outline of the research paradigms occurring in modern theories does not exhaust a variety of methodological approaches found in modern political theory. The article presents mainly paradigms of modern theory inter alia neofunctional, neoinstitutional, postbehavioral concept and also politics in the game theory perspective. It only concerns lines strictly connected with analyticalempirical theories. The problem of methodological foundations of normative theories is, however, very difficult to present. Although the researches noticed a necessity for their existence and development, the issue of rational justification of axiological opinions is still open. A lot of space is created to inspire the formation of political science metatheory base, not excluding referring to classical philosophy. At present it is difficult to explicitly identify philosophical and methodological foundations of the normative political theory. One may find reference to many different lines, from Thomism to sceptical conservatism and a variety of problems concerning hermeneutics and phenomenology. From the pos-positivistic point of view, ontological inspirations of the normative political theory in particular belong to metaphysics. For this reason the normative theory contributed little to empirical methodology. It is preferable to refer to genetic explanation, generalization and pre-scriptive monographic forms.